Behavioral Modeling of Typical Non-Ideal Analog to Digital Converter Using MATLAB - Taheri, Sayed Mostafa; Mohammadi, Bahareh (Transactions on Engineering and Computing Sciences, 2014)
Analog-to-digital converters (ADC) are one the most fundamental and crucial parts of an electronic device which needs to convert analog inputs into the digital format. Nowadays, you can find some type of ADCs in almost every communication device. Consequently, simulating an ADC plays a challenging and very fundamental role while aiming to simulate real-world instruments and designed systems. Despite the fundamental significance of this task, a general simulation model for typical non-ideal ADCs have not been presented yet. In this paper, we consider the most important non-ideality parameters of a typical ADC and initiate simulation models in the Simulink environment of MATLAB, as the most versatile widely-used simulation software for engineering tasks. For this purpose, we first reconsider the non-ideality parameters of a typical ADC from general perspective, aiming to bring a unified view in hand. Afterwards, the potential models for the non-ideality parameters are initiated separately, and then, are combined together to make the whole model. By creating a MATLAB Block of the whole general-topology model at the end, and defining the non-ideality parameters as variable inputs, we simulate the behavior of a typical ADC using practical non-ideality parameters data, and compare with an ideal ADC. This additionally enables a user interface for quick input of non-ideality parameters of any practical ADC for future clients. Despite the pure generality of the model, simulation results demonstrate acceptable outcomes proving the applicability of this model in wide range of engineering simulation tasks, and an appreciable step towards higher precision general simulations of typical ADCs.